Transcriptomic Time-Series Analyses of Gene Expression Profile During Zygotic Embryo Development in Picea mongolica - Yan, Jia; buer, Ha; Wang, Ya ping; zhula, Gegen; Bai, Yu´e (Frontiers in Genetics, 2021)
Zygotic embryogenesis is a critical process during seed development in gymnosperms. However, knowledge on the genome-wide transcriptional activation that guides this process in conifers is limited, especially in Picea mongolica. This tree species is endemic to semiarid habitats of Inner Mongolia in China. To extend what is known about the molecular events underpinning its zygotic embryogenesis, comparative transcriptomic analyses of gene expression in zygotic embryos were performed by RNA sequencing in P. mongolica. Our results showed that most changes in transcript levels occurred in the early embryonic pattering determination and formation of mature embryos. Transcripts related to embryogenic competence, cell division pattern, hormones, and stress response genes were identified during embryogenesis. Auxin is essential for early embryo patterning and pre-cotyledon embryonic formation. However, ABA is a major regulator of embryo maturation. Moreover, we found that methylation-related gene expression is associated with activation of early-stage embryos, late embryogenesis abundant proteins, and storage/energy-related genes with late and mature embryos. Furthermore, network analysis revealed stage-specific and multistage gene expression clusters during embryogenesis. WOX, MYB, AP2, and HLH transcription factors seem more relevant to embryogenesis in different stages. Our results provide large-scale and comprehensive transcriptome data for embryo development in P. mongolica. These data will lay a foundation for the protection and utilization of P. mongolica resources.